Prevalence and Short-Term Outcomes of Electrolyte Disorders in patients with Heart Failure - Zahoor Aslam Khan, Saeed Ahmed Alam, Asma Roshan, Attaullah, Saifullah, Sassi Manzoor Hassan (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Electrolyte abnormalities (EAs) are frequently observed in heart failure (HF) patients and are associated with worse short-term outcomes. This study aimed to assess the prevalence and short-term outcomes of electrolyte disorders in a cohort of heart failure patients. Methods: This retrospective cohort study included 180 hospitalized patients diagnosed with HF. The data on electrolyte levels, particularly sodium, potassium, calcium, and magnesium, were collected on admission and during hospitalization. Short-term outcomes such as 30-day mortality and readmission rates were analyzed. Results: The prevalence of electrolyte disorders was found to be 87%. Hyponatremia (36%) and hypokalemia (32%) were the most common disturbances. Both electrolyte disturbances were significantly associated with increased 30-day mortality (p < 0.05). Conclusion: Electrolyte disorders are prevalent in HF patients and are associated with adverse short-term outcomes. Prompt detection and correction of electrolyte imbalances may improve prognosis in these patients. Keywords: Electrolyte abnormalities, Heart failure, Hyponatremia, Hypokalemia, Short-term outcomes.